Host-Endolysins interactions - Nóbrega, Franklin Luzia (2013)
37 Host-Endolysins interactions Franklin L. Nobrega, Silvio Santos, Eugénio C. Ferreira, Joana Azeredo, Leon D. Kluskens IBB – Institute for Biotechnology and Bioengineering, Centre of Biological Engineering, Universidade do Minho, Campus de Gualtar, 4710-057 Braga, Portugal Abstract (Bacterio)phages are viruses that specifically infect bacteria. They are tremendously diverse and the most abundant living entities on Earth with an estimated total population size of 1031 phage particles. During infection they inject their DNA in the host bacteria and drive the cell machinery to produce new progeny phages. At the end of the infection cycle, phages (with the exception of a few known filamentous phages) produce enzymes called (endo)lysins that degrade the peptidoglycan (PG) leading to bacterial lysis and death in order to release the progeny virions. PG is a heteropolymer that protects the bacterial cell against osmotic pressure. The ability of endolysins to degrade PG causing the death of the bacterial cell makes these enzymes a very interesting biocontrol agent against problematic antibiotic resistant pathogenic bacteria. (..)